Inverter Sizing Ratio For Pv Plant In The Tropics - Lim, Winston Jun Liang (2021)
An inverter is used to convert the electricity generated by a photovoltaic (PV) system from direct current (DC) to alternating current (AC). The larger the power rating of an inverter, the higher the cost of the PV system. An inverter can cost more than 10 million ringgit for a 50 MW large-scale solar PV plant. Therefore, it can be downsized to save the capital cost because a PV system does not perform 100% of its rated capacity due to several losses. A specific term known as “inverter sizing ratio” (ISR) is used to show the ratio of DC power rating generate by the PV array to the ratio of AC power rating of the inverter. The drawback of downsizing (high ISR) is the possibility of power clipping during occasional high solar irradiance which leads to loss of income. There exists an optimal ISR to balance the amount of cost-saving and the amount of lost income. There is a lack of research study on optimal ISR in Malaysia despite some in other non-tropic countries. This study aims to provide a reference of optimal ISR for the PV industry in the tropics. The main objective of this study is to analyse the influence of the key parameters of a PV plant on the optimal ISR and levelised cost of electricity (LCOE) through sensitivity analysis. A special technique to divide the performance ratio into a fixed component and a variable component was used in this study based on the characteristic of the projects in the tropics. This technique helps to ease the sensitivity analysis. In addition, a method of processing the solar irradiance data which will affect the value of optimal ISR is adopted, compared and discussed. The solar irradiance data were sampled in a 5-minutes interval rather than averaged out within the time interval which was done by previous work. The sampled method means the solar irradiance data is taken for every X-minute interval for one year data where X can be five, ten, twenty, thirty or sixty minutes. The averaged method means the solar irradiance data in every X-minute interval is sum up then the data is averaged out with the value of X where X can be five, ten, twenty, thirty or sixty minutes. All the parameters in this study are the latest information on the PV industry. The graphs for sensitivity analysis were plotted and interpreted. The summary of all the sensitivity analysis was discussed. The sensitivity analysis of changing the specific cost of the PV system with the specific cost of the inverter has a great vi influence on optimal ISR. When the specific cost of the inverter is more expensive, it allows higher optimal ISR for saving cost. The recommended range for the optimal ISR is from 1.50-1.80 for a 10 MW plant in the tropics. In a nutshell, the results from this study can provide guidelines on choosing the right ISR for the PV industry player. Besides that, the PV industry player can estimate the percentage change for the optimal ISR when the sensitivity analysis is different from the nominal value via the trend of the lines plotted from the sensitivity analysis.